KEPADATAN POPULASI KEPINDING TANAH (Scotinophara coarctata) PADA TANAMAN PADI DI KENAGARIAN KOTO NAN TIGO KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Gusrianti, Eza; Jasmi, Jasmi; Indriati, Gustina (STKIP PGRI Sumbar, 2013)
ABSTRACT One of insect pests that attack the rice plant is Scotiphara coarctata ( Ladybug stink ) which is more known as the bedbug ground . This pest attacks the rice at the beginning of flowering . These pests suck fluids book on rice straw that caused crop color changed to reddish brown or yellow . In connection with that have done research on population density Scotinophara coarctata in rice on April 14 to August 15, 2013 . Sampling was conducted in Kenagarian Koto Nan Tigo Sub Trunk Cotton South Coastal District descriptive survey method and collections directly to Scotinophara coarctata that existed at the study site using adhesive traps . Collection using sampling techniques ordinal decision . Decision made for 2 days in a row 2 times ( morning and afternoon ) on flowering phase and phase cook milk . Decision made on 25 clumps of rice in each phase. From the results of research conducted in the flowering phase of the tail with 229 gained an average of 9.16 , and the phase of the cooking milk obtained 177 tail with an average 7.08 . From the results of research conducted in Kenagarian Koto Nan Tigo Sub Trunk Cotton South Coastal District earned an average population density is 406 bedbug ground tail with an average 16.24 perpengambilan . In this case bedbug ground already crossed a threshold .